Amoxicillin induced erythematous maculopapular rashes: a case report - Krishna Kumar, Dhakchinamoorthi; Rajganesh, Ravichandran; Jaya Shree, Dilli Batcha; Cherian, Sam Nikhil; Mohamed, Thayub (International Journal of Basic & Clinical Pharmacology, 2020)
Cutaneous adverse reactions (CAR) can occur with any class of drugs, however more widely caused by various antibiotics. Amoxicillin is a broad-spectrum, bactericidal, beta-lactam antibiotic, widely used for combating various infections. Cutaneous drug eruptions are known to be reported common while using penicillin class of drugs, specifically among children. These immune-mediated bizarre drug eruptions were range from mild to severe drug-induced cutaneous reactions, such as Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). The present case reported with maculopapular, erythematous rashes induced by amoxicillin in a nine-year-old male patient. Amoxicillin was prescribed for his hyperactive respiratory disease and subsequently after three days developed generalized maculopapular erythematous rashes as a result of an antibiotic-induced skin rash. The present case is being reported to add more data, also to emphasize and gather the information for evidence-based practice and to promote efficient pharmacovigilance adverse drug reaction reporting.